The Role of the Supervisory Board in Pre-School Educational Organizations (Eurasian Journal of Learning and Academic Teaching, 2023)
The President of the Republic of Uzbekistan Sh.M. Mirziyoyev states that "modern preschool education plays an important role in raising a healthy and mature generation." Currently, special attention is paid to preparing children for high-quality school education in preschool educational organizations under the jurisdiction of the Ministry of Preschool Education of the Republic of Uzbekistan. As a proof of this, in 2018, the coverage of children in the field of preschool education was 34.4%, and this indicator was 40.5% at the end of the half-year of 2019